APLIKASI SISTEM PAKAR DIAGNOSA PENYAKIT HEWAN PELIHARAAN - Pramudita, Arina (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Along with the development of technology, people’s need of information can be fulfill. People who have pets can use technology to help them learn various of information about their pets, one of it is the health of pets. Expert system is one of technology that mimics the works of a health experts in identifying a disease. This expert system is very useful especially when the pet’s owner do not have time to visit the vet. Therefore, it was made an expert system which can diagnose animal diseases and provide information about the disease, ways of handling / prevention as well as medicament to cope with the disease. This expert system application created with forward chaining inference method. The way of this expert system application work is by asking the owner of pet to choose the appropriate symptoms experienced by the pets, then the output is the possibility of disease experienced. Result of this final project is expected to help pet owners to be aware of information about pet illness quick.